Aptitudes of sweet potato genotypes for fresh consumption, ethanol production and animal feed - Gonçalves Neto, Álvaro Carlos; Maluf, Wilson Roberto; Gomes, Luiz Antonio Augusto; Gonçalves, Ranoel José de Sousa; Silva, Vanisse de Fátima; Lasmar, André (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to identify agronomic aptitudes of sweet potato (Ipomoea batatas) genotypes for fresh consumption, ethanol production, and animal feed, using aptitude indices. The aptitude indices were established as the weighted means of standardized variables for 16 traits of interest, using different weights for each trait according to the evaluated aptitude. The experimental design was a completely randomized block, with two replicates and 39 sweet potato genotypes: 36 accessions of the germplasm collection of Universidade Federal de Lavras (Brazil) and three commercial cultivars (Palmas, Brazlândia-Branca e Brazlândia-Rosada). Eight genotypes were considered apt to ethanol production, 11 to animal feed, and 11 to human consumption, including the cultivars Palmas and Brazlândia-Branca. The accessions UFLA07-12, UFLA07-31, UFLA07-43, UFLA07-49, and UFLA07-53 showed aptitude for ethanol production, animal feed and human consumption. The selection index is efficient in establishing aptitudes for sweet potato genotypes.